Professional up-skilling of English language lecturers (Pro-ELL) programme: the programme impact on Malaysian polytechnics and community college educators English proficiency - Yahaya, Nurhafizah; Ma'rof, Aini Azeqa (Politeknik Sultan Abdul Halim Mu'adzam Shah, 2020)
There are many studies reported on the poor grasp of English among students in Malaysia regardless of the education level. Meanwhile, often times the low level of proficiency in English language are associated with educators’ ability and competency to teach the subject. Thus, the strategy in focus is aimed at improving the quality of the English lecturers by introducing the Professional Up-skilling Program for English Language Lectures (Pro-ELL) among polytechnic and community college English language educators. Prior to the program, an online Versant test has been conducted to test the baseline score followed by Aptis test following the program. The findings revealed that majority of the participants successfully scored Band B2 and C1 after joining the Pro-ELL programme. Furthermore, they show satisfaction on the knowledge gained from the program and its effectiveness in improving their English proficiency. Overall, this study highlighted the effectiveness of Pro-ELL programme in assisting them to improve their English skills not just in teaching but learning.